The role of organizational commitment mediation on career development and employee performance - Yuesti, Anik; Adnyana, Imade Dwi (Nexo Revista Científica, 2022)
The article's main aim is to examine the role of organizational commitment mediation on career development and employee performance. This research is survey research, with a sample size of 82 selected with saturated samples. The results showed that quality of work-life and career development had a positive and significant effect on organizational commitment. Quality of work-life, career development and organizational commitment positively and significantly affect employee performance. Organizational commitment has not been able to mediate the indirect effect of quality of work life on employee performance. Organizational commitment has not mediated the indirect effect of career development on employee performance. It is recommended that the management organize Capacity building and family gathering activities to build teamwork among employees.